Supply Chain Bilateral Coordination with Option Contracts under Inflation Scenarios - Nana Wan; Xu Chen (Discrete Dynamics in Nature and Society)
There exist obvious changes in price and demand during the inflationary period, both of which are regarded as the key factors leading to supply chain uncertainty. In this paper, we focus our discussion on price increase and demand contraction caused by inflation, integrate the effect of inflation and option contracts within the model framework, and analyze how to use option contracts to achieve supply chain coordination under inflation scenarios. We consider a one-period two-stage supply chain consisting of one supplier and one retailer and explore the effect of inflation on the optimal ordering and production decisions under three different types of contracts: wholesale price contracts, option contracts, and portfolio contracts. Moreover, we explore the impact of option contracts on the supply chain through using wholesale price contracts model as the benchmark. We find that the retailer prefers adopting portfolio contracts, but the supplier prefers providing option contracts under inflation scenarios. Ultimately, option contracts will be implemented owing to the supplier’s market dominant position. In addition, we discuss the supply chain bilateral coordination mechanism with option contracts from the perspectives of two members and derive that option contracts can coordinate the supply chain and achieve Pareto improvement under inflation scenarios.